REGENERASI BALIAN WARA HINDU KAHARINGAN DAYAK LAWANGAN KECAMATAN DUSUN TENGAH KABUPATEN BARITO TIMUR - edung, Tardi (Dharma Duta, 2023)
The activities of the religious life of the Hindu Kaharingan people of the Dayak Lawangan tribe in carrying out religious ceremonies require personnel or individuals who are ready to use, in this case the implementation of the wara ritual religious ceremony. Energy or people to carry out the wara existence ritual is needed, especially nowadays the number is very limited. The Wara Ritual is passed down by the ancestors to generations in a traditional manner, a form of accountability to the ancestors to the next generation. The theory for analyzing using constructivism seeks to build and rearrange to return to the way it was.Balian wara regeneration research is a socio-religious research. The design uses a qualitative descriptive method. Types of qualitative data, primary and secondary data sources. Data collection techniques carried out simultaneously, observation, interviews. Data Analysis Techniques using a flow analysis model divided into four stages of activity. Analysis is a series of research activities to support understanding (understanding).The results of the research process of regeneration of Balian Wara of the Hindu Kaharingan tribe of Dayak Lawangan consist of: a) own will, a candidate has a high desire and commitment to learn. b) studying, a candidate for balian wara seeks a teacher using oral tradition methods to gain meaning. c) ngawit nginte, acquiring balian knowledge by means of a balian wara tuha transferring balian knowledge to a candidate for balian wara. d) ngayak ngajun, a balian wara tuha demands and directs a balian wara candidate. And e) suntutus, a candidate for balian wara does repetitions when using the sacred mantra balian or asks his teacher for an explanation.